Educational level, gender and health practices regarding COVID-19 in N'Djamena, Chad: A cross-sectional study - G. Rodrigue T. Dzomo; Margarita Bernales; Carlos Gomez-Virseda; Francis Deassal; Rodrigo Lopez (AOSIS, 2022)
COVID-19 is affecting different countries and populations unequally. In this sense, sub-Saharan countries represent a particularly vulnerable context due to their unique demographic and health circumstances. A holistic approach to Covid-19 is urged, one that considers the social-cultural contexts of people's lives. Using Social Determinants of Health (SDH) as framework, we explore which variables could explain the differences in health practices regarding the prevention of COVID-19 in Chad, in order to propose recommendations that allow communities to better face future health crises. The study was designed as a cross-sectional survey conducted in N'Djamena, Chad, using a convenience sampling technique that included 2,330 participants. A regression model was fitted to assess the relationship between educational level, gender, and health practices regarding COVID-19. 2,269 participants completed the survey successfully. Participants mean age was 31.04, 61.52% were male, and 40.55% had precarious jobs. 21.38% of participants answered right all questions regarding knowledge and 37.19% followed all preventive measures. Findings show that safe practices regarding COVID-19 depend on right knowledge. Gender influences knowledge mainly through its influence on education. Vulnerability is given by women's reduced access to education. The SDH approach provide with an exploratory explanation and some recommendations aimed at local authorities. Access to education for all men and women must be improved to increase health practices and better deal with future health crises.